The honoured teacher and docent Petras Rumšas (1921 11 02–1987 02 23) merits to Lithuanian school - Jasiūnas, Henrikas; Verikaitė, Vitolda (Lietuvos matematikos rinkinys, 2021)
It is represented the Petras Rumšas works which reveal the impact this man had on schools, education and culture in Lithuania.
Keywords: university; school; mathematics; textbooks; problem books; history; review; translation